Multicultural Classroom Management of Students in Elementary Schools - Mastur Mastur (AL-ISHLAH: Jurnal Pendidikan, 2023)
This research aims to determine how teachers manage classes in elementary schools in multicultural educational settings. Elementary school teachers must design a learning process that integrates multicultural education so that teachers contribute positively to fostering students' nationalism and multicultural attitudes from an early age. The introduction of multiculturalism aims to shape the character of a country's children who can accept, understand, and respect all people of different races, personalities, social, ethnic, customs, and religions. Efforts to learn multicultural education in elementary schools must be carried out as a means of training and awareness for the younger generation so that they can accept and appreciate all multicultural differences. The research approach used is qualitative by conducting a literature review. The data analysis technique of this research is descriptive qualitative using the content analysis method. The results of this study are that multicultural education in elementary schools is systemic and holistic and needs to be developed based on national culture and character. The strategies teachers use in managing multicultural classrooms are an important part of realizing the lofty ideals of building the next generation who have the traits and characteristics of respecting, tolerating, and being fair to others regardless of their social background, ethnicity, religion, race, and class.